The preparation and characterization of Sinabung volcanic ash as silica based adsorbent - Lisnawaty Simatupang; Devi Devi (Pascasarjana Universitas Negeri Medan, 2016)
Abstract. Synthesis of silica gel with sol-gel method has been carried out by utilizing the volcanic ash from Mount Sinabung taken from Berastepu village, Simpang Empat, Karo within 1.5 km from the summit of Mount Sinabung. Volcanic ash is one of the largest source of silica, potentially as materials for silica gel. Synthesis of silica gel in this study conducted by sol-gel method. Volcanic ash didekstruksi with 4M NaOH solution and gel formation with 3M HCl solution. Characterization of silica performed by AAS analysis, FTIR and XRD. Silica levels obtained in this study amounted to 17.85%. Based on the results of using FTIR analysis showed a cluster Si-O-Si and Si-OH stating that the silica adsorbent was successfully created. Characterization using XRD showed that the silica produced has a low degree kekristalan (amorphous form).Keywords: adsorbents, silica, volcanic ash mount Sinabung